Flight to liquidity and systemic bank runs - Roberto Robatto (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
This paper presents a general equilibrium, monetary model of bank runs to study monetary injections during financial crises. When the probability of runs is positive, depositors increase money demand and reduce deposits; at the economy-wide level, the velocity of money drops and deflation arises. Two quantitative examples show that the model accounts for a large fraction of (i) the drop in deposits in the Great Depression, and (ii) the 400 billion run on money market mutual funds in September 2008. In some circumstances, monetary injections have no effects on prices but reduce money velocity and deposits. Counterfactual policy analyses show that, if the Federal Reserve had not intervened in September 2008, the run on money market mutual funds would have been much smaller.
Keywords: E44; E51; G20; 330; Monetary Injections; Flight to Liquidity; Bank Runs; Endogenous Money Velocity; Great Depression; Great Recession; Money Market Mutual Funds